Paradoks odbiranja tvitov na javni radioteleviziji - Vobič, Igor (Javnost (Ljubljana), 2014)
By studying the collection, selection and inclusion of contents from Twitter in pre-election debates at the Slovenian public broadcaster, the article recognises the conflict between stimulating participatory practices, on the one hand, and maintaining a privileged role of traditional gatekeepers, on the other. By analysing qualitative data gathered through observations in the newsroom and in-depth interviews with key actors, the author intertwines organisational context, established routines and individual factors, and identifies the paradox of gatekeeping tweets during Slovenian public television debates before the European elections in 2014. The study indicates institutional protection of gatekeeping privileges at the expense of more open communication, while at the same time gatekeeping is exclusively framed by the subjective schemes of the identified gatekeepers. This paradox has important implications for self-understanding of journalism and indicates subjective civic empowerment, which in itself does not mean participatory action, but only strengthening the sense of the ability to participate in political life. In addition, based on the results of the study, it seems that journalism of traditional media does not have adequate answers for its transforming structural position in social communication, organisational problems of media houses, and contingent identification of journalists.
Keywords: Slovenia; Slovenija; television; televizija; televizijske oddaje; RTV Slovenija; Radiotelevizija Slovenija; election; volitve; politična kampanja; gledalci